Water Scarcity and Its Economic Consequences - The Case of India - Do, Khanh Linh (2025)
This thesis explores the economic causes and consequences of water scarcity in India, a country facing one of the most acute water crises of the 21st century. Despite having sufficient freshwater resources, India struggles with widespread water stress due to inefficient irrigation practices, overexploitation of groundwater, pollution, population growth, urbanization, and inadequate governance. The findings reveal that water scarcity has significant economic impacts, particularly in the agricultural sector, which consumes nearly 78% of the country’s water but suffers from low efficiency and declining productivity. Industrial activity, public health, employment, and GDP growth are also affected. The thesis further explores mitigation strategies, including demand-side management, improved water governance, investment in infrastructure, and the revival of traditional water harvesting systems. The case of Rajasthan demonstrates the potential of community-based solutions to enhance resilience in drought-prone regions. The paper concludes that water scarcity in India is not merely an environmental issue but a multidimensional development crisis with serious economic implications. Addressing it requires urgent, coordinated, and sustainable policy action.